2018
DOI: 10.1007/s00127-018-1621-z
|View full text |Cite
|
Sign up to set email alerts
|

Suicide risk among native- and foreign-origin persons in Sweden: a longitudinal examination of the role of unemployment status

Abstract: Purpose Prior research has documented an association between unemployment and elevated suicide risk. Yet, few Swedish studies have explicitly considered how such risk may vary by different migration background characteristics among persons of foreign-origin, who often experience diverse forms of labor market marginalization. This study examines the extent to which unemployment status may differentially influence suicide risk among the foreign-origin by generational status, region of origin, age at arrival, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Potential hypothesis to explain these increased mental health effects are exposure to discrimination and racialization in the workplace, followed by continued disadvantages across generations (eg, lack of intergenerational economic mobility and perpetuation of lower socioeconomic positions). In addition, these effects could be exacerbated by divided cultural identities, such as limited sense of belonging or lack of social connection of native born) (27,28,47). Interestingly, we see female first-generation migrant workers, especially from non-EU countries in low-quality employment trajectories, had a much higher risk of CMD compared to female Swedish-born of Swedish background.…”
Section: Discussionmentioning
confidence: 73%
“…Potential hypothesis to explain these increased mental health effects are exposure to discrimination and racialization in the workplace, followed by continued disadvantages across generations (eg, lack of intergenerational economic mobility and perpetuation of lower socioeconomic positions). In addition, these effects could be exacerbated by divided cultural identities, such as limited sense of belonging or lack of social connection of native born) (27,28,47). Interestingly, we see female first-generation migrant workers, especially from non-EU countries in low-quality employment trajectories, had a much higher risk of CMD compared to female Swedish-born of Swedish background.…”
Section: Discussionmentioning
confidence: 73%
“…Indeed, it is noteworthy that unemployment only accounted for a small percentage of the regional variation in suicides, and thus, there may be other factors that better explain the regional differences in suicides. In addition, Dunlavy et al (2019) have suggested that the magnitude of the effect of unemployment on suicide varies with migration background characteristics and is smaller for non‐European immigrants and those with shorter periods of Swedish residency. If this is correct, it is possible that the increasing growth of refugees in rural municipalities, that is, more migrants with shorter periods of residence, may help explain the observed decrease in suicide rates among non‐European immigrants in rural municipalities.…”
Section: Discussionmentioning
confidence: 99%